The Epistemology of Ecological Tafsir and the Transformation of The Interpretation of Kawniyyah Verses in Classical and Contemporary Exegesis - Siti Nurkhafifah Marisa; Triansyah Fisa; Edy Saputra; Hanif Hanif; T Mairizal; Muhammad Nur Mirwan; Tabsyir Masykar; Muhammad Faisal (Darul Ilmi Bina Insan Foundation, 2026)
This study examines the development of Qur’anic exegesis from an ecological perspective, highlighting the epistemological shift from classical to contemporary interpretations. The primary focus of this study was the analysis of QS. al-Baqarah: 30 and QS. ar-Rum: 41 in the tafsirs of Al-Tabari, Ibn Kathir, Quraish Shihab, and Hamka. This study employed a library research method using qualitative, hermeneutical, philosophical, and comparative approaches. The findings reveal that classical exegesis tends to be textual-normative, with a strong reliance on transmitted narrations (riwayat) to understand the concepts of khalifah (vicegerency) and fasad (corruption), thereby positioning nature primarily in a theological domain. In contrast, contemporary exegesis demonstrates a shift toward a contextual-ecological approach that emphasizes environmental balance and human responsibility, as in Khalifah. Quraish Shihab and Hamka, in particular, relate environmental destruction to modern ecological crises such as pollution, deforestation, and climate change. This study further demonstrates that ecological tafsir emerged from the awareness of the global environmental crisis and the need to reinterpret the Qur’an’s kauniyah verses integratively. Thus, ecological exegesis functions not only as a textual interpretation but also as a foundation for environmental ethics grounded in Qur’anic values that are relevant to the challenges of the modern era. This research is expected to strengthen the integration of Qur’anic studies and environmental issues within contemporary Islamic academic discourse, while also contributing theoretically to the development of an interpretive paradigm that is responsive to global ecological problems and the sustainability of human life in the modern age